Pengetahuan Dan Persepsi Masyarakat Terhadap Cagar Alam Raya Pasi Kota Singkawang - Irwan Lovadi, Hangi Aziarsih, Rizalinda (Jurnal Protobiont, 2014)
Raya Pasi Nature Reserve is located in Singkawang region of West Kalimantan that is managed by Natural Resources Conservation Agency of Department of Forestry. By gathering data which was related to the knowledge and attitude of the people toward nature reserve and biodiversity can avoid the conflict among local people and conservation area management. The aim of this study was to investigate the knowledge and attitude of the people toward the conservation area and protected plant conservation in Raya Pasi Nature Reserve. This study was conducted in 3 months from March to May 2012. The data was collected by random sampling quetionaire technique and interview which was given to the resident from three villages adjacent to Raya Pasi Nature Reserve, i.e.Pangmilang village, Bagak Sahwa village, and Sagatani village. The result showed that most resident from those villages know about Raya Pasi Nature Reserve and they generally understand about its function. The resident from those three villages have the knowledge and general perception about the plants which protected by the government. Based on the survey, it is known that26% people from those villages got the information and knowledge fromtelevision and only about 5% people got it from the newspaper.